KADAR N TERMINAL-PRO BRAIN NATRIURETIC PEPTIDE PADA PENDERITA PENYAKIT JANTUNG HIPERTENSI - Febria Asterina; B Nasution; N Akbar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2007)
Patients with hypertension are at high risk for development of Left Ventricle Hypertrophy (LVH) and Left Ventricular Systolic Dysfunction (LVSD). These conditions should be identified earlier to prevent cardiac morbidity and mortality. To measured serumlevel of NT-proBNP in hypertensive and mild symptomatic Hypertensive Heart Disease (HHD) patients (NYHA class I-II), to performechocardiography evaluation to all of the patients and associated with serum level of NT-proBNP. A cross sectional study was done at H.Adam Malik Hospital Medan, participants were recruited from consecutive samples of 15 hypertensive and 16 mild symptomatic HHDpatients whose visited cardiovascular and internal medicine out patient clinics. Of these patients, blood samples were taken and a twodimension echo-Doppler study was performed. The patients divided into three groups based on echocardiography studies respectively:Group 1: 9 hypertensive patients with normal echocardiography finding; group 2: 13 patients with LVH and ejection fraction (EF) ≥60%; and group 3: 9 patients with LVH and EF < 60%. Mean NT-proBNP serum level (in pg/mL) for groups 1-3 respectively, were:56.4 ± 34.5, 245.4 ± 339.2 and 852.0 ± 1218.9. Mean NT-proBNP serum level differed among all three groups (p = 0.050), butthe significant difference found between group 1 and group 3 (p < 0.05) only. There were significant correlation between NT-proBNPserum level and the three stages of echocardiography finding (r = 0.488 and p = 0.005). The result suggests that NT-proBNP serumlevel correlated with deterioration of heart function and structure according echocardiography studies. The Significant rise in NT-proBNPserum level happened only when Left Ventricular Systolic Dysfunction (LVSD) develops in hypertension.